A Pluralist Objection Against the No-Miracle Argument (Culturas Científicas, 2021)
The aim of this article is to elaborate an objection against the realist argument that, in the debate on scientific realism, is known as the ‘No-Miracles Argument’ (NMA). This argument hinges on the assumption that scientific realism is the philosophy that best explains the success of science. Here, it is objected that if the considerations from scientific pluralism are to be taken seriously, there is no univocal conception of «success» at hand. From this it follows that either we are not able to infer theory’s «truth» from theory’s «success», or that we must accept that science offers several truths about the same inquiry’s domain. I outline three solutions to face this issue: first, to defend the NMA against the pluralist’s objections, nevertheless there is no account in the literature that can meet these objections. Second, either to reconceptualize the notion of «truth» or embrace a metaphysical pluralism, yet these accounts are highly counterintuitive. Finally, to dispense the NMA from scientific realism debate, and, instead, to assume an empiricist pluralism that can account for sciences’ plurality without a compromise with alternative notions of «truth» or metaphysical interpretations of scientific pluralism.
Keywords: Scientific realism; Scientific pluralism; Inference to the best explanation; Empiricism